2016
DOI: 10.1111/psyp.12784
|View full text |Cite
|
Sign up to set email alerts
|

Acute exercise has a general facilitative effect on cognitive function: A combined ERP temporal dynamics and BDNF study

Abstract: This study examined whether acute moderate intensity exercise results in a general or selective improvement in cognitive function. In addition, multiple stimulus-locked ERP components and serum BDNF levels were assessed to investigate potential neurobiological mechanisms underlying acute exercise effects on select aspects of cognitive performance. Thirty young adults were recruited and participated in exercise and reading control sessions in a counterbalanced order. Following treatments, the Stroop task was ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
82
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(110 citation statements)
references
References 75 publications
23
82
3
2
Order By: Relevance
“…Interestingly, prior research has suggested that acute exercise resulted in an increase in conflict detection indexed by the shorter N450 latency [86], suggesting the differential effects of acute exercise on the stages of conflict processing in young adults. In contrast to young adults, preadolescent children exhibit evidence of reduced conflict SP amplitude following acute exercise, which might be interpreted as a reduction in the interference effect and increased conflict-processing ability.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, prior research has suggested that acute exercise resulted in an increase in conflict detection indexed by the shorter N450 latency [86], suggesting the differential effects of acute exercise on the stages of conflict processing in young adults. In contrast to young adults, preadolescent children exhibit evidence of reduced conflict SP amplitude following acute exercise, which might be interpreted as a reduction in the interference effect and increased conflict-processing ability.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, her/his cardiorespiratory fitness (VO 2 max ) and absolute strength were assessed following the procedures described previously. 1,5 Briefly,VO 2 max was estimated using the submaximal YMCA Ergometer Test 26 with a cycle ergometer (Ergoselect 200 P, Ergoline, Germany), and absolute strength was assessed following 10-repetition maximum (RM) guidelines 27 for leg press, leg extension, chest press, chest fly, lateral pull down, right bicep curl, and left bicep curl. Notably, practice taskswitching trials were also administered until correct responses reached the 80% level; this ensured sufficient test familiarisation.…”
Section: Methodsmentioning
confidence: 99%
“…The intensities chosen for AE and RE have been associated with beneficial effects on EF. 1,13 The detailed protocols for AE 1 , RE 13 and the control 13 sessions have been published. Briefly, the AE session entailed cycle ergometry for 30 min; specifically, a 5-min warm-up, 20 min of moderate-intensity exercise [i.e., 60-70% of maximal heart rate (HR) reserve), and a 5-min cooldown.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations